Learning Deficits in Adult Mitochondria Carrier Homolog 2 Forebrain Knockout Mouse. (1st December 2018) - Aloni, Etay; Ruggiero, Antonella; Gross, Atan; Segal, Menahem
Highlights: MTCH2 BKO results in loss of spatial learning but not motor skills in middle aged mice. This is associated with an age-dependent loss of long-term potentiation in CA1 region of the hippocampus. These experiments highlight the role of mitochondria malfunction in hippocampus-dependent memory. Abstract: Mitochondrial Carrier Homolog 2 (MTCH2) acts as a receptor for the BH3 interacting-domain death agonist (BID) in the mitochondrial outer membrane. Loss of MTCH2 affects mitochondria energy metabolism and function. MTCH2 forebrain conditional KO (MTCH2 BKO) display a deficit in hippocampus-dependent cognitive functions. Here we study age-related MTCH2 BKO behavioral and electrophysiological aspects of hippocampal functions. MTCH2 BKO exhibit impaired spatial but not motor learning and an impairment in long-term potentiation (LTP) in hippocampal slices. Moreover, MTCH2 BKO express an increase in activated microglia, in addition to a reduction in neuron density in the hippocampus, but do not express amyloid-β plaques or neurofibrillary tangles. These results highlight the role of mitochondria in the normal hippocampus-dependent memory formation.